Bio-based thermosetting epoxy foams: mechanical and thermal characterization - Altuna, Facundo Ignacio (2015)
Thermosetting epoxy foams were synthesized by replacing the commercial synthetic epoxy resin by a biogenic epoxidized vegetable oil. Foam formulations were developed avoiding the use of amine hardeners, organic volatile compounds (OVCs), and ozone depleting or flammable foaming gases. The produced biobased foams were evaluated in terms of mechanical and thermal properties. It was found that the glass transition temperature (Tg) is somewhat lower than that corresponding to synthetic epoxy foams, but mechanical properties are similar when comparing foams of the same density. Moreover, the possibility of obtaining foams in a wide range of densities (160–550 kg/m3) makes these systems a sound alternative to commercial available formulations.